The quality of strained yoghurt consumed in konya - The quality of strained yoghurt consumed in Konya (Eurasian Journal of Veterinary Sciences)
In this research, chemical and microbiological qualities of 14 strained yoghurt samples taken from Konya market were determined. It was found that microbiological qualities of strained yoghurt samples were low and chemically 78.57 % of samples differed from the values of Food Regulation.